The Reference and the Significance of Agricultural Commodities in Punjabi Folk Songs - Batool, Saima; Hussain, Fayyaz; Sarfraz, Maryam (sourcecoder, 2023)
The fertile and beautiful land of punjab is known as the land of melodies. Folk songs are the treasure of the culture and civilisation of any nation. As we flip the pages of history we get to know about the government system which was imposed in that particular era and who was the ruler of that period. However the history remains silent for the culture and civilisation of this era. At this time folk songs are the only source through which we can see the images of the history. The land of Punjab is enriched with the beautiful and tuneful folk songs. This area is also know as the “land of folk songs,” because here from birth to death and everything who bear a relationship with this land especially plants, fruits, flowers, trees and basic commodities are mentioned in these songs. These songs are full of life to such an extent that for every reader and listener has a deep impact on their hearts and minds. The folk songs of everylocality are originated from their own respective regions and the culture of that region is certainly reflected in its folk songs. Punjab is an agricultural land that is why it’s agricultural comodities are mentioned in these folk songs with various references.In this research paper it has been tried to explain the common commodities of the Punjab like gandum ,kpass,jwar,bajra,chnyand makai their use in folk songs in different aspects as well as importance of these crops.